The Analysis of Broken Cap Brand Violation (Study of Decisions in Mahkamah Agung (Number 85 / Pk / Pdt.Sus-Haki / 2015) (International Journal of Psychosocial Rehabilitation, 2020)
In the global environment, every company carries out economic activities such as producing a product that could be purchased by the public and accepted by the society. The intended strategy is in producing a product, the product is expected to have its own attraction, then the product must be given a Brand as a sign. The Trademark Case is the subject of this study, i.e. in the dispute over ownership of the "Cap Kaki Tiga" Brand, this mark was accused by Russell Vince, a Plaintiff in the Commercial Court, saying that Wen Ken Drug Co. was a company. Pte. Ltd, as the owner of the Brand Cap Kaki Tiga has imitated the symbol of the British country Isle of man. This thesis produce the formulation of the problem on how legal protection of Foreign Trademarks in Indonesia and the legal consequences for the Cap Kaki Tiga brand after the decision Number 85 / PK / PK / Pdt.Sus-HaKI / 2015. This thesis uses the normative juridical method. The author also obtained primary, secondary and tertiary data sources Including agreements between countries such as TRIPs agreements or agreements governing other trademarks. In protecting foreign brands in Indonesia, efforts that can be made are preventive and repressive efforts. The legal consequences after the verdict that is, causing Cap Kaki Tiga does not get legal protection for their brand in Indonesia.